Transformation of the Role of Educational Supervisors in the Digital Era: Adaptation Strategies and Supervision Innovations - Zoya F. Sumampow; Melisa Veronika Tudus (Jurnal Masyarakat Digital, 2024)
This qualitative study investigates the evolving landscape of educational supervision in the digital age, focusing on competency requirements, paradigm shifts, and infrastructural needs. Through extensive literature analysis, the research identifies key transformational patterns in supervisory roles and responsibilities. The study reveals three critical findings. First, supervisors must develop comprehensive digital competencies encompassing technical skills, digital literacy, and online pedagogical expertise. This transformation requires structured professional development programs and continuous learning opportunities to ensure effective supervision in digital environments. Second, the supervision paradigm is transitioning from traditional hierarchical models to collaborative approaches. This shift emphasizes peer learning, shared responsibility, and dynamic interaction between supervisors and educators. Digital platforms facilitate this transformation by enabling real-time feedback, virtual collaboration, and data-driven decision-making processes. Third, successful digital supervision requires robust technological infrastructure and supportive policies. This includes reliable digital platforms, secure data management systems, and clear guidelines for online supervision practices. Policy frameworks must adapt to accommodate new supervision modalities while ensuring quality standards and educational objectives are maintained. The research concludes that effective digital transformation in educational supervision demands a comprehensive strategy incorporating pedagogical innovation, technological advancement, managerial efficiency, and policy adaptation. This multidimensional approach should consider both immediate practical needs and long-term strategic objectives in educational supervision. Recommendations include developing targeted professional development programs, establishing flexible supervision frameworks, and creating supportive policy environments that promote digital innovation while maintaining educational quality standards.